Kingdom of the Netherlands-Netherlands Selected Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper for the Netherlands highlights that Dutch cost competitiveness deteriorated significantly in the years prior to 2004. The relatively poor economic performance during the new millennium contributed to these concerns generally, as did restrained export performance more specifically. The deceleration of private consumption growth started earlier than the deceleration of per capita real disposable income growth, and occurred at a time when the unemployment rate has been at a historic low and interest rates had declined.